2020
DOI: 10.1097/rhu.0000000000001314
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Toxicity After Initiating Immune Checkpoint Inhibitor Treatment in Patients With Rheumatoid Arthritis

Abstract: Introduction: Immune checkpoint inhibitors (ICIs) are increasingly used to treat advanced cancer. Rheumatoid arthritis (RA) is associated with an increased risk of malignancies; however, patients with RA have been excluded from ICI trials. In this study, we evaluated risk of toxicity after initiation of ICI treatment in RA patients. Methods:We conducted a single-institution, medical records review analysis to assess the incidence of immune-related adverse events (irAEs) and autoimmune disease (AID) flares amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 27 publications
(69 reference statements)
1
17
0
Order By: Relevance
“…A close interdisciplinary collaboration for managing ICI toxicity is recommended [ 59 ]. Patients need to be informed that even quiescent rheumatoid arthritis can flare during ICI treatment [ 60 ], and that symptoms may persist after treatment discontinuation. Increasing experience of ICI use in patients with autoimmune disorders will help to better delineate which patients can safely receive ICI.…”
Section: Discussionmentioning
confidence: 99%
“…A close interdisciplinary collaboration for managing ICI toxicity is recommended [ 59 ]. Patients need to be informed that even quiescent rheumatoid arthritis can flare during ICI treatment [ 60 ], and that symptoms may persist after treatment discontinuation. Increasing experience of ICI use in patients with autoimmune disorders will help to better delineate which patients can safely receive ICI.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis of Xie et al ( 52 ) reported that the pooled incidence of AID flare and newly developed irAEs were 35% and 33%, respectively, and there was no statistical difference between patients with and without immunosuppressive therapy regarding AID flare. Besides, almost all AID flares occurred at the beginning of ICI therapy—2 weeks to 1 year after initiation, but mostly around 1–2 months ( 15 , 27 , 29 , 31 , 33 , 41 ). Most AID flares had similar manifestations and affected the same anatomic sites as prior AID symptoms ( 27 , 31 , 36 ).…”
Section: Literature Experience With Icis In Aid Patientsmentioning
confidence: 99%
“…The authors found that while most patients were clinically quiescent prior to initiating immunotherapy for malignant conditions, at least 50% of patients flared, which seems to support data from other series. 64 Overall, these findings suggest that ICIs lead to similar rates of irAEs in patients with pre-existing AIDs compared with those without existing AID and are summarized in table 1.…”
Section: Open Accessmentioning
confidence: 72%